The 'endo-blue method' for direct cloning of restriction endonuclease genes in E. coli. - Fomenkov, A (1994)
A new E. coli strain has been constructed that contains the dinD1::LacZ+ fusion and is deficient in methylation-dependent restriction systems (McrA-, McrBC-, Mrr-). This strain has been used to clone restriction endonuclease genes directly into E. coli. When E. coli cells are not fully protected by the cognate methylase, the restriction enzyme damages the DNA in vivo and induces the SOS response. The SOS-induced cells form blue colonies on indicator plates containing X-gal. Using this method the genes coding for the thermostable restriction enzymes Taql (5'TCGA3') and Tth111l (5'GACNNNGTC3') have been successfully cloned in E. coli. The new strain will be useful to clone other genes involved in DNA metabolism.